An acoustic power antibacterial quantum dot spray film forming wound dressing and a preparation method and application thereof
Patent Information
- Application Number
- CN202611096840.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-23
AI Technical Summary
[0007]针对现有成膜敷料在大面积不规则烧伤创面覆盖一致性不足、抗感染手段易耐药或驻留时间短,以及声动力量子点在创面环境中易被稀释/冲刷、分布不均且难以与成膜覆盖一体化等问题,本发明提供一种可喷涂、可原位快速成膜的创面敷料,使其在深Ⅱ度烧伤等渗出丰富、不规则的大面积创面上实现快速连续成膜封闭,并在超声触发下实现稳定、可控、广谱的抗感染作用,同时兼顾喷涂可操作性与生物安全性
1、本发明的创面敷料喷涂后能够在大面积不规则创面实现快速原位成膜与稳定覆盖,适配大面积不规则创面。本发明采用EDA-HA(A组分)与OHA(B组分)原位动态共价交联,可在创面表面实现“喷涂-铺展-交联-成膜”的快速完成,形成连续膜层,解决贴片类敷料在不规则/大面积创面上贴合不良、边缘渗漏与覆盖不连续的问题,尤其适用于深Ⅱ度烧伤等形态复杂且渗出丰富场景。
Smart Images

Figure CN122604999B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical materials technology, and in particular to a wound dressing with acoustically powered antibacterial quantum dot spray film formation, its preparation method and application. Background Technology
[0002] Deep second-degree and deeper burns are often characterized by large areas, irregular shapes, and abundant exudate. Early and timely wound closure is crucial for reducing infection and improving treatment success rates. While traditional gauze / oil gauze can provide coverage, it is prone to adhesion, causing pain during dressing changes and secondary damage, hindering continuous repair and infection control. Pre-fabricated patch-type hydrogel / foam dressings lack sufficient adherence and continuous closure on large, irregular wounds, easily leading to edge lifting and exudate channels, resulting in decreased barrier function, and frequent dressing changes increase the risk of infection. Therefore, dressings that can form films in situ and adapt to complex morphologies have become the development direction. In recent years, sprayable hydrogels have emerged, mostly achieving rapid film formation through "spraying-spreading-in-situ cross-linking," suitable for irregular wounds, dynamic sites, and emergency scenarios. Common implementation paths include: ① Physical crosslinking / shear thinning system: good sprayability, but often insufficient mechanical strength, toughness, and resistance to exudation and erosion. It is easily damaged under conditions of exudate erosion, joint movement, or friction; ② Temperature-sensitive / photocuring system: can achieve in-situ gelation, but the gelation time is uncontrollable and is affected by the environment (temperature, humidity, pH, etc.) or requires additional light source equipment. On-site operation is complicated and affects the consistency of on-site film formation; it is highly dependent on equipment (such as the need for light source or high-pressure equipment) and has poor accessibility in battlefield / emergency scenarios; ③ Dynamic covalent crosslinking system: using natural polysaccharides such as hyaluronic acid as the backbone, by introducing reactive groups such as aldehyde groups and amino / hydrazide groups, and utilizing Schiff base bonds / hydrazone bonds to achieve faster crosslinking and tissue adhesion. A typical example is the two-component instant-mix and spray strategy composed of oxidized hyaluronic acid (OHA) and amino / hydrazide-modified hyaluronic acid; this type of system can complete gelation and film formation within a certain time and enhance wet adhesion through the reaction of aldehyde groups with amino groups of tissue proteins. However, the reaction kinetics of such systems, which involve mixing and spraying two components to form a film, are difficult to control. If the reaction kinetics are too fast, a non-uniform structure with local "outer layer cross-linking first" may be formed in the early stage of droplet deposition, which restricts subsequent interdiffusion and uniform reaction, resulting in a dispersion of the film cross-linking gradient and performance. On the other hand, if the reaction kinetics are too slow, it will cause sagging, prolonged film formation time, and poor adhesion.
[0003] Burn infection is a common burn complication and a significant cause of death. Topical antibacterial agents are advantageous for burn wounds with poor deep circulation. Existing topical anti-infective dressings mainly include: silver preparations such as silver sulfadiazine, antibiotic-containing dressings / hydrogels, silver-containing nanomaterial dressings, and antimicrobial peptide dressings. Among these, antibiotic-loaded hydrogels can achieve sustained release through a material network; if a dynamic covalent network is used, a certain degree of pH-responsive release can be achieved by utilizing the slightly acidic environment of the infection. While topical antibiotics can rapidly inhibit bacteria, long-term or improper use can easily induce drug-resistant bacteria. Although silver preparations are widely used, their compatibility with biofilms, drug-resistant bacteria, and different stages of infection remains limited, and some systems may introduce cytotoxicity or affect re-epithelialization. Relying solely on a single "chemical sterilization" mechanism is insufficient to achieve sustained, controllable, and low-risk anti-infective effects in the complex microenvironment of infection.
[0004] Sonodynamic therapy utilizes ultrasound to excite sonosensitive agents to generate reactive oxygen species (ROS), triggering oxidative stress in bacteria and thus killing microorganisms. It features non-invasiveness, deep tissue penetration, and relatively low susceptibility to inducing drug resistance. Existing sonosensitive agents include organic sonosensitive agents such as porphyrins and inorganic nanomaterials such as TiO2, ZnO, and MOFs. Inorganic materials may still be limited in terms of aqueous dispersibility, energy conversion, and ROS yield. Quantum dots, due to their band gap and electron-hole excitation characteristics, have good potential for ROS generation under ultrasound excitation; metal ion doping can introduce "intermediate energy levels" to increase energy transfer paths and reduce energy loss, thereby improving sonodynamic efficiency. Therefore, sonodynamic antibacterial quantum dots have been proposed for anti-infection treatment and wound management. However, when sonodynamic antibacterial quantum dots are used as "standalone drugs / dispersions," there are challenges in retention and controlled delivery. If quantum dot sonosensitive agents are applied directly to the wound in solution / suspension form, the following issues may arise: ① They are easily diluted or washed away in exudative environments, making it difficult to maintain an effective concentration and duration of action on the wound surface; ② Nanoparticles may aggregate or be unevenly distributed, leading to spatially uneven ROS generation and insufficient local efficacy; ③ The sonodynamic process requires material and microenvironment matching. If a suitable carrier is lacking to achieve stable loading, continuous retention, and controlled release / exposure, the consistency of clinical operation and overall efficacy will be limited. Currently, there is a lack of integrated solutions for "film formation coverage" and "sonic dynamic antibacterial treatment" applicable to large-area deep second-degree burns.
[0005] Existing technologies often achieve the goals of "rapid wound closure" and "highly effective infection control" in a fragmented manner: either emphasizing film-forming adhesion but with limited antibacterial capabilities, or emphasizing antibacterial properties (such as topical drugs / nanosound-sensitive agents) but lacking stable retention and barrier sealing. Especially in deep second-degree burn scenarios with large areas, complex morphologies, and high infection risks, there is still an urgent need for a composite dressing system that can be sprayed to form a rapid film, has tissue adhesion / barrier functions, and can generate ROS under ultrasonic triggering to achieve antibacterial effects. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a wound dressing that can be sprayed and formed into a film in situ using sonic dynamics antibacterial quantum dots, as well as its preparation method and application.
[0007] To address the problems of existing film-forming dressings, such as insufficient uniformity of coverage on large, irregular burn wounds, easy resistance to anti-infection treatments, or short residence time, as well as the difficulty in integrating sonodynamic quantum dots with film-forming coverage due to easy dilution / washing and uneven distribution in the wound environment, this invention provides a sprayable, in-situ rapid film-forming wound dressing that enables rapid and continuous film formation and closure on large, irregular wounds with abundant exudate, such as deep second-degree burns. Under ultrasonic triggering, it achieves stable, controllable, and broad-spectrum anti-infection effects, while also taking into account the operability of spraying and biosafety.
[0008] The wound dressing of this invention utilizes in-situ dynamic covalent cross-linking of ethylenediamined hyaluronic acid (EDA-HA) (component A) and oxidized hyaluronic acid (OHA) (component B). Under conditions of irregular, large-area wounds with abundant exudate, the dressing can quickly complete the "spraying-spreading-cross-linking-film formation" process, forming a continuous and dense film layer. This film layer provides physical barrier and isolation protection, while also meeting on-site fixation requirements such as wet adhesion / mechanical interlocking, thus solving the problems of rapid coverage and shape adaptability.
[0009] The wound dressing of this invention also utilizes hydrophilic acoustic-dynamic antibacterial quantum dots. The quantum dots stably enter the aqueous phase and are compatible with the EDA-HA / OHA system. After the introduction of acoustic-dynamic antibacterial quantum dots, the system can still maintain good atomization sprayability and film uniformity, avoiding phenomena such as abnormal viscosity / rheology, limited droplet spreading, and increased cross-linking gradient of the film layer due to particle introduction. This ensures film stability under different batches and operating conditions, solves the problem of spraying and film formation consistency of composite systems, and solves the risks of quantum dot aggregation, sedimentation, local enrichment, and nozzle clogging in composite formulations. It achieves stable and uniform distribution and controllable loading of quantum dots in the film layer, so that they maintain effective action sites and effective concentrations at the wound interface.
[0010] The wound dressing of this invention fixes quantum dots in a cross-linked network through in-situ film formation, reducing the loss of quantum dots in the exudative environment of burn wounds, improving the retention of acoustic sensitizers and their resistance to erosion, and forming a functional layer with high retention and low loss at the wound interface. In the environment of continuous flushing of wound exudate, it solves the problem of acoustic sensitizers being easily diluted and lost, resulting in short action time. It achieves local retention and controllable exposure (or controllable release) of quantum dots at the membrane / wound interface, ensuring that sufficient ROS can be generated under ultrasonic triggering conditions and achieve a continuous and broad-spectrum killing effect on common pathogens (including drug-resistant bacteria / biofilm-associated bacteria), thereby reducing dependence on traditional antibiotics or high-dose silver preparations.
[0011] The wound dressing of the present invention, by controlling a specific pH value and adding an appropriate amount of quantum dots, achieves sonodynamic antibacterial ability while controlling the risk of irritation / cytotoxicity of the composite system to tissues and cells, reducing potential systemic absorption or long-term residue risks, and solving biocompatibility and safety issues; it also takes into account the clinical dressing change needs, so that the membrane layer can be controlled to be removed or moderately degraded when needed, avoiding secondary damage and difficulty in dressing changes.
[0012] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a wound dressing for sonodynamic antibacterial quantum dot spray film formation, the wound dressing comprising separately packaged component A and component B, and sonodynamic antibacterial quantum dots dispersed in component A and / or component B. Component A is a solution containing ethylenediamined hyaluronic acid (EDA-HA), which is obtained by reacting carboxyl-activated hyaluronic acid with ethylenediamine; the mass fraction of ethylenediamined hyaluronic acid (EDA-HA) in component A is 5%~20%; Component B is a solution containing oxidized hyaluronic acid (OHA), wherein the degree of oxidation of the oxidized hyaluronic acid (OHA) is 15%~40%. The pH values of both component A and component B are 6.0 to 7.5. The sonodynamic antibacterial quantum dots are hydrophilic sonodynamic antibacterial quantum dots.
[0013] This invention utilizes nucleophilic groups such as NH2 / -NH- provided by EDA-HA to react with -CHO provided by OHA to form a Schiff base reaction, thereby achieving rapid in-situ film formation after spraying. It also utilizes acoustically dynamic antibacterial quantum dots as the antibacterial functional component of the dressing, enabling the dressing to generate ROS under external ultrasound after film formation, thus achieving on-demand killing of pathogenic microorganisms on the wound surface.
[0014] The wound dressing of this invention utilizes component A with a specific EDA-HA content, component B with a specific degree of oxidation of OHA, and a specific pH, combined with hydrophilic acoustic antibacterial quantum dots. This not only meets the requirements for biocompatibility but also enables effective atomized spraying. After spraying, a stable and continuous film can be formed within 30s to 180s, uniformly dispersing and fixing the quantum dots in the film. This film can resist the scouring and dilution of wound exudate and has high scouring resistance. The spray-formed film has good uniformity and high consistency. At the same time, the film can be stably attached to the wound through wet adhesion and mechanical interlocking, resulting in good film stability.
[0015] The wound dressing of this invention must utilize a specific amino-modified hyaluronic acid derivative, EDA-HA; not just any amino-modified hyaluronic acid can be used as component A. Under the conditions of "high-pressure aerosol spraying without a carry-over agent," component A must simultaneously meet the requirements of aerosol spraying rheological window and sufficient film-forming crosslinking activity. If the selected amino-modified hyaluronic acid has excessively high viscosity or insufficient shear thinning at the target solid content, it will lead to unstable aerosol spraying, intermittent spraying, or even failure to spray, resulting in discontinuous film formation or localized accumulation. Experiments of this invention show that when using hydrazide-modified hyaluronic acid (ADH-HA) as component A, the solution viscosity increases significantly under the solid content conditions required for film strength, making it difficult to achieve stable aerosol spraying under high-pressure aerosol spraying conditions. This results in intermittent spraying, uneven droplet distribution, or nozzle clogging, leading to discontinuous film formation or localized accumulation. Under the same solid content as EDA-HA, stable film formation is still difficult to achieve after more than 180 seconds.
[0016] In comparison, ethylenediamined hyaluronic acid (EDA-HA) has better solubility and viscosity that makes it easier to fall into the sprayable window, achieving stable atomization and uniform spreading, and taking into account the comprehensive performance of "atomization sprayability + rapid film formation consistency + wet adhesion / mechanical interlock + quantum dot dispersion stability".
[0017] As a preferred embodiment of the wound dressing of the present invention, the wound dressing includes separately packaged components A and B, and sonodynamic antibacterial quantum dots dispersed in component A.
[0018] In a preferred embodiment of the wound dressing of the present invention, the degree of amination of ethylenediamined hyaluronic acid in component A is 15% to 40%; and the mass fraction of oxidized hyaluronic acid (OHA) in component B is 5% to 20%.
[0019] The coupling between the degree of amination and mass fraction of ethylenediamined hyaluronic acid and the degree of oxidation and mass fraction of oxidized hyaluronic acid described in this invention can form a stable spray film-forming effect.
[0020] In a preferred embodiment of the wound dressing of the present invention, the mass fraction of ethylenediamined hyaluronic acid (EDA-HA) in component A is 5%~15%; the degree of amination of the ethylenediamined hyaluronic acid (EDA-HA) is 20%~35%. The "amine group density / degree of amination" of the EDA-HA of the present invention can be adjusted according to the film-forming speed and mechanical requirements to match the aldehyde group density of OHA, avoiding problems such as uneven droplet deposition due to excessively rapid crosslinking or sagging and poor film formation due to excessively slow crosslinking. EDA-HA with this degree of amination can achieve rapid and uniform in-situ crosslinking film formation within the spray window, while also considering wet adhesion / mechanical interlocking and spray stability.
[0021] In a preferred embodiment of the wound dressing of the present invention, the mass fraction of oxidized hyaluronic acid (OHA) in component B is 5%~15%; the oxidation degree of oxidized hyaluronic acid (OHA) is 20%~35%. The "aldehyde density / oxidation degree" of the OHA of the present invention can be adjusted according to the film-forming speed and mechanical requirements to match the amino density of EDA-HA, avoiding problems such as uneven droplet deposition due to excessively rapid crosslinking or sagging and poor film formation due to excessively slow crosslinking. OHA with this oxidation degree can achieve rapid and uniform in-situ crosslinking film formation within the spray window, while also considering wet adhesion / mechanical interlocking and spray stability.
[0022] In a preferred embodiment of the wound dressing of the present invention, the mass fraction of ethylenediamined hyaluronic acid (EDA-HA) in component A is 7%; the degree of amination of ethylenediamined hyaluronic acid (EDA-HA) is 28%; the mass fraction of oxidized hyaluronic acid (OHA) in component B is 10%; and the degree of oxidation of oxidized hyaluronic acid (OHA) is 30%.
[0023] In a preferred embodiment of the wound dressing of the present invention, the solvents for components A and B include water or a buffer solution.
[0024] In a preferred embodiment of the wound dressing of the present invention, the water includes sterile water or deionized water; the buffer solution includes buffers such as PBS buffer.
[0025] In a preferred embodiment of the wound dressing of the present invention, the volume ratio of component A to component B in the wound dressing is (0.5~2):1.
[0026] In a preferred embodiment of the wound dressing of the present invention, the volume ratio of component A to component B in the wound dressing is 1:1.
[0027] In a preferred embodiment of the wound dressing of the present invention, the mass fraction of sonodynamic antibacterial quantum dots in the wound dressing is 0.01% to 0.2%. This content of sonodynamic antibacterial quantum dots can balance the sonodynamic antibacterial efficacy, film-forming uniformity, and biocompatibility of the dressing.
[0028] As a preferred embodiment of the wound dressing of the present invention, the mass fraction of sonodynamic antibacterial quantum dots in the wound dressing is 0.02%~0.15%.
[0029] In a preferred embodiment of the wound dressing of the present invention, the mass fraction of acoustic-dynamic antibacterial quantum dots in the wound dressing is 0.05%.
[0030] As a preferred embodiment of the wound dressing of the present invention, the hydrophilized sonodynamic antibacterial quantum dots are hydrophilized by ligand exchange using hydrophilic ligands.
[0031] By using ligand exchange with hydrophilic ligands such as mercaptopropionic acid (MPA), the hydrophobic ligands on the surface of the sonodynamic antibacterial quantum dots are replaced with hydrophilic ligands. The thiol groups in the hydrophilic ligands such as mercaptopropionic acid (MPA) bind to the surface of the quantum dots, and their hydrophilic carboxyl groups endow them with water solubility. Under alkaline conditions, the deprotonation of the carboxyl groups further enhances the stability of the aqueous phase dispersion.
[0032] In a preferred embodiment of the wound dressing of the present invention, the hydrophilic ligand includes mercaptopropionic acid (MPA), mercaptoacetic acid, mono-mercaptopolyethylene glycol, mercapto-polyethylene glycol-carboxyl, etc. The mono-mercaptopolyethylene glycol includes PEG2000-SH, and the mercapto-polyethylene glycol-carboxyl includes SH-PEG3500-COOH.
[0033] As a preferred embodiment of the wound dressing of the present invention, the hydrophilic acoustic-dynamic antibacterial quantum dots are hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs).
[0034] The silver-doped zinc sulfide quantum dots (ZnS:Ag QDs) used in this invention were prepared according to the literature "Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situ sonodynamic antimicrobial therapy for biomedical implants" (doi: 10.1016 / j.cej.2024.155694).
[0035] As a preferred embodiment of the wound dressing of the present invention, the hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs) have a particle size of 2~10 nm, preferably 3~5 nm.
[0036] As a preferred embodiment of the wound dressing of the present invention, the preparation method of the hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs) is as follows: silver-doped zinc sulfide quantum dots (ZnS:Ag QDs) are dispersed in a nonpolar solvent, then an alcohol solvent and an alkaline solution are added and mixed well, followed by the addition of mercaptopropionic acid (MPA) and thorough mixing and reaction, and allowed to stand for phase separation; the organic phase is removed, the aqueous phase is taken and acetone is added, the precipitate is collected by centrifugation, the precipitate is washed and dried to obtain hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs).
[0037] As a preferred embodiment of the wound dressing of the present invention, in the preparation method of the hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs), the nonpolar solvent includes chloroform, toluene, n-hexane, etc.; the alcohol solvent includes methanol, ethanol, isopropanol, etc.; and the alkaline solution includes NaOH solution or KOH solution.
[0038] As a preferred embodiment of the wound dressing described in this invention, the solution of component A and / or component B further contains excipients. Without departing from the spirit of this invention, to improve the uniformity of spray film formation, inhibit quantum dot aggregation and sedimentation, reduce the risk of nozzle clogging, and improve film flexibility, while also being compatible with high-pressure aerosol cans without carry-over agents (high-pressure aerosol cans without carry-over agents are similar to high-pressure water spray cans, using compressed air or compressed inert gas as the driving medium, without the need for liquefied propellants or carry-over agents), component A and / or component B may contain a small amount of excipients to improve sprayability and film flexibility, but their amount should be controlled to avoid significantly weakening the crosslinking reaction rate of EDA-HA and OHA and the uniformity of film formation.
[0039] In a preferred embodiment of the wound dressing of the present invention, the excipients include dispersants / stabilizers, moisturizers / plasticizers, osmotic pressure regulators, buffer solutions, or adhesion / wetting modifiers. The adhesion / wetting modifiers are used to improve spreading and wet adhesion.
[0040] As a preferred embodiment of the wound dressing of the present invention, the dispersant / stabilizer includes PVP, PEG, poloxamer (Poloxamer 188 / 407), etc., to enhance the colloidal stability of hydrophilic quantum dots in aqueous phase and polysaccharide solution.
[0041] In a preferred embodiment of the wound dressing of the present invention, the moisturizing / plasticizing agent includes glycerin, sorbitol, propylene glycol, etc., to improve the flexibility and crack resistance of the membrane layer.
[0042] In a preferred embodiment of the wound dressing of the present invention, the osmotic pressure regulator includes NaCl, and the buffer solution includes PBS buffer; the osmotic pressure regulator and the buffer solution improve physiological compatibility and user comfort.
[0043] The method for testing the degree of amination described in this invention is the ¹H NMR integral method.
[0044] The oxidation degree test method described in this invention is the hydroxylamine hydrochloride titration method.
[0045] Secondly, the present invention provides a method for preparing the above-mentioned acoustic-dynamic antibacterial quantum dot spray film-forming wound dressing. Component A and component B are aseptically treated and then aseptically dispensed into a spraying device. Before aseptic treatment, hydrophilic acoustic-dynamic antibacterial quantum dots are added to component A and / or component B and dispersed evenly to obtain the wound dressing.
[0046] As a preferred embodiment of the preparation method of the present invention, the preparation method comprises at least one of the following (I) to (III): (I) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component A from step S1 and disperse them evenly to obtain component A containing quantum dots. S4. Sterilize the quantum dot-containing component A from step S3 and the component B from step S2, and then aseptically dispense them into the spraying device to obtain the wound dressing. (II) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component B from step S2 and disperse them evenly to obtain component B containing quantum dots. S4. Sterilize the quantum dot-containing component B from step S3 and the component A from step S1, and then aseptically dispense them into the spraying device to obtain the wound dressing. (III) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component A from step S1 and component B from step S2, and disperse them evenly to obtain component A containing quantum dots and component B containing quantum dots. S4. The quantum dot-containing component A and quantum dot-containing component B from step S3 are sterilized separately, and then aseptically dispensed into a spraying device to obtain the wound dressing.
[0047] As a preferred embodiment of the preparation method described in this invention, before mixing with component A and / or component B, the hydrophilic acoustic-dynamic antibacterial quantum dots are first uniformly dispersed using a dispersant / stabilizer or a solvent of component A and / or component B. This operation can further improve the quantum dots' resistance to exudate erosion and long-term dispersion stability, reduce the risk of local enrichment and sedimentation of quantum dots, and improve the dispersion stability and intrafilm distribution uniformity during high-pressure atomization spraying.
[0048] In a preferred embodiment of the preparation method of the present invention, the preparation method is (I), which includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component A from step S1 and disperse them evenly to obtain component A containing quantum dots. S4. The quantum dot-containing component A from step S3 and component B from step S2 are sterilized separately, and then aseptically dispensed into a spraying device to obtain the wound dressing.
[0049] This invention has found that mixing hydrophilic acoustic antibacterial quantum dots with component A results in a wound dressing with better sprayability, higher film-forming consistency, stronger erosion resistance, and better stability of the quantum dots; it also provides better overall performance in terms of atomization sprayability, rapid film-forming consistency, wet adhesion / mechanical interlocking, and quantum dot dispersion stability.
[0050] In a preferred embodiment of the preparation method described in this invention, the spraying device is a high-pressure aerosol can.
[0051] In a preferred embodiment of the preparation method described in this invention, the high-pressure aerosol can is a high-pressure aerosol can without carry-over agent.
[0052] In a preferred embodiment of the preparation method described in this invention, the spraying device is a dual-cavity spraying device or two single-cavity spraying devices; the dual-cavity spraying device utilizes a dual-channel mixing nozzle to simultaneously spray component A and component B; the two single-cavity spraying devices spray component A and component B sequentially according to a sequential spraying strategy. The nozzle orifice diameter, spray velocity, and spray distance of the spraying device are designed to ensure stable atomization, no significant dripping, and no clogging; those skilled in the art can select and optimize these parameters as needed.
[0053] This invention dispenses the raw materials of wound dressing into a spray device, and components A and B are sprayed out sequentially or simultaneously. The spray quickly forms a film for the protection and treatment of wounds.
[0054] Thirdly, the present invention provides the application of the above-mentioned wound dressing in the preparation of dressing products for treating burn wounds.
[0055] Fourthly, the present invention provides a dressing product for burn wounds, wherein the dressing product is formed by self-crosslinking of the above-mentioned wound dressing.
[0056] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The wound dressing of this invention, after spraying, can achieve rapid in-situ film formation and stable coverage on large, irregular wounds, making it suitable for large, irregular wounds. This invention uses EDA-HA (component A) and OHA (component B) for in-situ dynamic covalent cross-linking, enabling rapid completion of "spraying-spreading-cross-linking-film formation" on the wound surface, forming a continuous film layer. This solves the problems of poor adhesion, edge leakage, and discontinuous coverage of patch-type dressings on irregular / large wounds, and is especially suitable for complex morphological scenarios with abundant exudation, such as deep second-degree burns.
[0057] 2. The dressing film layer formed after the wound dressing of the present invention is sprayed forms a stable covering layer on the surface of moist tissue. On the one hand, it provides a physical barrier to reduce the risk of exogenous contamination and secondary damage. On the other hand, it achieves more reliable interface adhesion by means of dynamic covalent bond network and material spreading behavior, which helps to reduce dressing displacement and exudate channel formation, improve the effect of continuous care, and improve the reliability of on-site fixation and care.
[0058] 3. This invention hydrophilizes ZnS:Ag quantum dots, enabling them to stably enter the aqueous phase and be compatible with the EDA-HA / OHA system, while maintaining the consistency of EDA-HA / OHA system spraying and film formation. This significantly reduces the risk of quantum dot aggregation and sedimentation in the system and nozzle clogging. At the same time, it helps to achieve uniform distribution of quantum dots in the spray-formed film, avoiding the local enrichment, increased crosslinking gradient, and film performance dispersion caused by the introduction of traditional nanoparticles.
[0059] 4. This invention fixes / semi-fixes quantum dots in a cross-linked network through in-situ film formation, reducing the loss of quantum dots in the exudative environment of burn wounds, improving the retention and erosion resistance of the sound-sensitive agent, forming a functional layer with high retention and low loss at the wound interface, prolonging the effective action time and improving the consistency and repeatability of antibacterial intervention.
[0060] 5. This invention utilizes exogenous ultrasound to trigger quantum dots to generate ROS, achieving broad-spectrum antibacterial and a broader anti-infection strategy with lower drug resistance risk through a non-antibiotic mechanism. It can kill bacteria on demand and has the potential advantages of on-demand activation, controllable action area, and weak correlation with drug resistance mechanisms. It is suitable for early control of high-risk burn wounds.
[0061] 6. This invention uses an A / B two-component packaging and matching spraying device to achieve rapid film formation and coverage. The antibacterial function is triggered when needed by common ultrasonic means, without relying on light sources or complex environmental conditions. The function and operation are integrated, making it suitable for multiple on-site / emergency and clinical applications such as battlefield rescue, disaster relief, pre-hospital emergency care and in-hospital burn wards, improving the accessibility of technology and the feasibility of clinical translation.
[0062] 7. By adjusting the concentrations of EDA-HA and OHA, the ratio of A to B, the functional group density, and the excipient system, this invention can achieve adjustable film formation time, film mechanical properties, and flexibility while ensuring sprayability. At the same time, the quantum dot loading can be designed in gradients within the safe range of this invention, which facilitates the optimization of solutions for different infection risks, wound sizes, and nursing frequencies.
[0063] 8. The wound dressing of the present invention takes into account the spray application, film formation consistency, biocompatibility and clinical dressing change requirements, and provides an integrated solution for "rapid coverage" and "triggerable anti-infection" of burn wounds, with strong overall usability. Attached Figure Description
[0064] Figure 1 The image shows product diagrams of components A and B in Example 1 of this invention. Figure 2 This is a schematic diagram of component A and component B of the wound dressing containing quantum dots in Embodiment 1 of the present invention. In the diagram, A is component A containing quantum dots and B is component B. Figure 3 This is the film-forming state of the wound dressing sprayed onto the glass plate in Embodiment 1 of the present invention; Figure 4 The film-forming effect of the wound dressing sprayed onto the surface of pigskin in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram illustrating the preparation and application method of the wound dressing of the present invention; Figure 6 This invention utilizes the reaction principle of cross-linking between component A and component B to form a film; Figure 7 The effect of the wound dressing of Embodiment 1 of the present invention on Staphylococcus aureus on a plate coating. Figure 8 The effect of the wound dressing of Embodiment 1 of the present invention on Escherichia coli on a plating plate. Figure 9 The results of MTT cell viability assay on L929 cells using the wound dressing of Example 1 of this invention; Figure 10 The effect of the wound dressing of Embodiment 1 of the present invention on the burn wound repair process. Detailed Implementation
[0065] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0066] The following is some information about the materials used in the embodiments: 1. Ethylenediamined hyaluronic acid (EDA-HA): Amination degree of 15%, 28%, or 40%, wherein the molecular weight of HA is 100,000 to 500,000 Da; the EDA-HA used in this invention can be commercially available or prepared in-house using the following method, which includes the following steps: (1) Dissolve hyaluronic acid (HA) in 0.1 M MES buffer (pH 5.5) to obtain HA solution; add activator under stirring to activate the carboxyl group of HA (activation for 10 min) to obtain activated HA solution; (2) Dissolve ethylenediamine in MES buffer and adjust the pH to 5.5, then slowly add it dropwise to the HA activation solution in step (1). Stir the reaction at room temperature for 24 h, and control the pH in the range of 5.4 to 5.6 during the reaction. (3) After the reaction was completed, the reaction solution was purified by dialysis using a MWCO 1 kDa dialysis bag. First, the reaction solution was dialyzed in 5% NaCl solution for 2 days, and then dialyzed in deionized water for 3 days to remove unreacted small molecules and byproducts. After dialysis, the pH of the dialysate was adjusted to 7.5-8.0, and the solution was lyophilized to obtain EDA-HA, which was stored at 4℃ for later use. By adjusting the proportion of raw materials, EDA-HA with different degrees of amination was obtained.
[0067] 2. Oxidized Hyaluronic Acid (OHA): Oxidation degrees include 10%, 15%, 30%, 40%, and 45%, where the molecular weight of HA is 500,000 to 2,000,000 Da. The OHA used in this invention can be commercially available or prepared in-house using the following method: Dissolve hyaluronic acid (HA) in deionized water and stir thoroughly until completely dissolved to obtain an HA solution. Dissolve NaIO4 in deionized water and add it to the HA solution in the dark. Stir and react at room temperature in the dark for 24 hours to introduce aldehyde groups (-CHO). After the reaction is complete, add ethylene glycol (to terminate the oxidation reaction) and continue the reaction for 2 hours. Purify the reaction solution by dialyzing it through a MWCO 3500 Da dialysis bag under dark conditions for 3 days (changing the water multiple times daily) to remove oxidants and small molecules. After dialysis, adjust the pH of the dialysate to 7.0-7.5, freeze-dry to obtain OHA, and store at 4°C in the dark for later use. By adjusting the proportions of the raw materials, OHA with different oxidation degrees can be obtained.
[0068] 3. Silver-doped zinc sulfide quantum dots (ZnS:Ag QDs): with a particle size of 3~5 nm. The ZnS:Ag QDs used in this invention were prepared according to the literature "Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situsonodynamic antimicrobial therapy for biomedical implants" (doi: 10.1016 / j.cej.2024.155694), and the preparation method includes the following steps: (1) Oleic acid (10 mL), oleylamine (20 mL) were mixed with AgNO3 (0.34 g) and Fe(NO3)3·9H2O (0.08 g), and heated at 120 °C for 1 h to react completely. Ethanol was added at a volume ratio of 1:3 to precipitate the precipitate. The precipitate was purified by centrifugation (8000 rpm, 15 min), and the precipitate was collected to obtain silver nanoparticles (Ag NPs). (2) Mix 128 mg of sulfur powder with 10 mL of oleylamine and 10 mL of oleic acid, heat at 100 °C for 40 min to obtain a sulfur source precursor solution; disperse the Ag NPs obtained in step (1) in toluene to obtain an Ag NPs dispersion; mix 0.350 mL of Ag NPs dispersion with 6 mL of toluene and 3 mL of sulfur source precursor solution, react at 60 °C in a water bath for 1 h, precipitate with ethanol and purify by centrifugation to obtain silver sulfide nanoparticles (Ag2S NPs), dissolve in 12 mL of toluene to obtain an Ag2S NPs toluene solution for later use (counted as one sample); (3) Add 0.2 mL of oleic acid, 0.1 mL of oleylamine and 1 mL of methanol solution of Zn(NO3)2⋅6H2O with a concentration of 0.1 g / mL to the Ag2S NPs toluene solution in step (2), and add 0.1 mL of TBP (to promote the exchange / doping process). React fully at 60 °C for 2 h. After the reaction is complete, a precipitate is obtained. After centrifugation and purification, hydrophobic ligand-coated silver-doped zinc sulfide quantum dots (ZnS:Ag QDs) are obtained.
[0069] 4. ADH-HA: The degree of amination is 15%~40%, and the molecular weight of HA is 0.3~20,000 Da. The ADH-HA used in this invention is prepared according to the literature Ren H. et al. Injectable, self-healing hydrogeladhesives with firm tissue adhesion and on-demand biodegradation for sutureless wound closure. Science Advances 2023; 9(33): eadh4327. DOI:10.1126 / sciadv.adh4327.
[0070] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.
[0071] Example 1 1. Preparation of hydrophilic silver-doped zinc sulfide quantum dots (ZnS:Ag QDs) Preparation method of hydrophilic ZnS:Ag QDs: 500 mg of silver-doped zinc sulfide quantum dots (ZnS:Ag QDs) were dispersed in 5 mL of chloroform, then methanol (4 mL) and 30 wt% NaOH aqueous solution (800 μL) were added and mixed well. Then mercaptopropionic acid (MPA, 400 μL) was added and stirred vigorously at room temperature for about 30 min. After standing for 10 min, the layers were separated. The organic phase was removed, and acetone was added to the aqueous phase to precipitate and centrifuged (6000 rpm, 8 min). The precipitate was collected and washed to remove residual solvent and free ligands. After drying, hydrophilic ZnS:Ag QDs (powder) were obtained.
[0072] 2. Wound dressing formed by acoustic-dynamic antibacterial quantum dot spray and its preparation method This wound dressing comprises separately packaged components A and B, as well as sonodynamic antibacterial quantum dots dispersed in component A. Component A is an aqueous solution of ethylenediamined hyaluronic acid (EDA-HA), wherein the mass fraction of EDA-HA in component A is 7% and the degree of amination of EDA-HA is 28%. Component B is an aqueous solution of oxidized hyaluronic acid (OHA), wherein the mass fraction of OHA in component B is 10% and the degree of oxidation of OHA is 30%. The acoustic-dynamic antibacterial quantum dots are hydrophilic silver-doped zinc sulfide quantum dots (hydrophilic ZnS:Ag QDs). In the wound dressing, the volume ratio of component A to component B is 1:1, and the mass fraction of acoustic-dynamic antibacterial quantum dots in the wound dressing is 0.05%; the pH value of both component A and component B is 6.8.
[0073] In this embodiment, the product diagrams of component A and component B are as follows: Figure 1 As shown.
[0074] The preparation method of this wound dressing includes the following steps: (1) Dissolve EDA-HA in sterile water and adjust the pH to obtain component A; (2) Dissolve OHA in sterile water and adjust the pH to obtain component B; (3) Mix the hydrophilic ZnS:Ag QDs with the A component from step (1), and use magnetic stirring and gentle dispersion to obtain a uniform dispersion (avoid strong conditions affecting the activity of OHA functional groups) to obtain the A component containing quantum dots; (4) Filter and sterilize the quantum dot A component in step (3) and the B component in step (2) respectively, and then sterilely dispense them into high-pressure aerosol cans without carry-over agents to obtain a two-component wound dressing.
[0075] The aforementioned wound dressing is used to treat burn wounds. The method of application is as follows: The burn wound is routinely cleaned, rinsed, and hemostatically controlled. Components A and B, containing quantum dots, are sprayed onto the wound sequentially or simultaneously. The wound dressing cross-links in situ on the wound and stabilizes into a film within 180 seconds. After film stabilization, an outer protective dressing can be applied as needed clinically. When anti-infection intervention is required, exogenous ultrasound is applied to the film area to trigger a sonodynamic process. Ultrasound parameters can be selected within a clinically acceptable range to achieve effective ROS generation and antibacterial effects while ensuring safety.
[0076] The product illustration of the two-component wound dressing containing quantum dots, components A and B, in this embodiment is shown below. Figure 2 As shown in the figure, A is component A containing quantum dots, and B is component B.
[0077] In this embodiment, the quantum dot-containing component A of the two-component wound dressing is first sprayed onto a glass plate, followed by component B. After spraying for 30 seconds and allowing it to stand, a continuous, uniform, stable, and transparent film layer forms on the glass plate in approximately 180 seconds. The film-forming state of the wound dressing sprayed onto the glass plate is as follows: Figure 3 As shown.
[0078] Before dispensing the quantum dot-containing components A and B in this embodiment, equal proportions of blue dye were added to prepare a blue dye-containing wound dressing. Then, the dye-containing quantum dot-containing component A was first sprayed onto the surface of pigskin, followed by the dye-containing component B. After spraying for 30 seconds and allowing it to stand for approximately 180 seconds, a continuous, uniform, and stable blue film layer formed on the pigskin surface. The film-forming effect of the wound dressing sprayed onto the pigskin surface is as follows... Figure 4 As shown.
[0079] A schematic diagram of the preparation and application scheme of the wound dressing of the present invention is shown below. Figure 5 As shown.
[0080] This invention utilizes the reaction principle of cross-linking film formation between component A and component B, as follows: Figure 6 As shown, a dynamic covalent cross-linked network is formed by the Schiff base reaction between the nucleophilic groups such as NH2 / -NH- provided by EDA-HA and the -CHO provided by OHA, thereby achieving rapid in-situ film formation after spraying.
[0081] Example 2-3 This invention provides two embodiments of a sonodynamic antibacterial quantum dot spray-formed wound dressing and its preparation method. Embodiments 2-3 have the same components as the wound dressing in Embodiment 1, differing only in the component mixed with hydrophilic silver-doped zinc sulfide quantum dots in the preparation method. Specifically, Example 2: The preparation method of the wound dressing includes the following steps: (1) Dissolve EDA-HA in sterile water and adjust the pH to obtain component A; (2) Dissolve OHA in sterile water and adjust the pH to obtain component B; (3) Mix the hydrophilic ZnS:Ag QDs with the B component of step (2), and use magnetic stirring and gentle dispersion to obtain a uniform dispersion (avoid strong conditions affecting the activity of EDA-HA functional groups) to obtain the B component containing quantum dots; (4) Filter and sterilize component A in step (1) and component B containing quantum dots in step (3), and then sterilely dispense them into high-pressure aerosol cans without carry-over agents to obtain two-component wound dressings.
[0082] Example 3: The preparation method of the wound dressing includes the following steps: (1) Dissolve EDA-HA in sterile water and adjust the pH to obtain component A; (2) Dissolve OHA in sterile water and adjust the pH to obtain component B; (3) Divide the hydrophilic ZnS:Ag QDs into two parts (the total mass fraction of hydrophilic ZnS:Ag QDs in the wound dressing in this embodiment is the same as that in Example 1, which is also 0.05%), and mix them with component A in step (1) and component B in step (2) respectively. Use magnetic stirring and gentle dispersion to obtain a uniform dispersion, and obtain component A containing quantum dots and component B containing quantum dots. (4) The A component containing quantum dots and the B component containing quantum dots in step (3) are filtered and sterilized, and then sterilely dispensed into high-pressure aerosol cans without carry-over agents to obtain a two-component wound dressing.
[0083] Examples 4-6 The present invention provides three embodiments of a sonodynamic antibacterial quantum dot spray-formed wound dressing and its preparation method. The differences between Embodiments 4-6 and Embodiment 1 are only in the mass fraction of EDA-HA in component A and the mass fraction of OHA in component B; specifically, Example 4: Compared with Example 1, the mass fraction of EDA-HA in component A of the wound dressing in Example 1 was adjusted from 7% to 5%, and the mass fraction of OHA in component B was adjusted from 10% to 5%. Example 5: Compared with Example 1, the mass fraction of EDA-HA in component A of the wound dressing in Example 1 was adjusted from 7% to 15%, and the mass fraction of OHA in component B was adjusted from 10% to 15%. Example 6: Compared with Example 1, the mass fraction of EDA-HA in component A of the wound dressing in Example 1 was adjusted from 7% to 20%, and the mass fraction of OHA in component B was adjusted from 10% to 20%. The preparation methods for the wound dressings in Examples 4-6 are the same as in Example 1.
[0084] Examples 7-8 Two embodiments of the acoustic-dynamic antibacterial quantum dot spray film-forming wound dressing and its preparation method of the present invention are provided. The difference between the wound dressing of Embodiment 7-8 and Embodiment 1 lies only in the degree of amination of EDA-HA and the degree of oxidation of OHA in components A and B, respectively. Specifically, Example 7: Compared with Example 1, the amination degree of EDA-HA in component A of the wound dressing in Example 1 was adjusted from 28% to 15%, and the oxidation degree of OHA in component B was adjusted from 30% to 15%. Example 8: Compared with Example 1, the degree of amination of EDA-HA in component A of the wound dressing in Example 1 was adjusted from 28% to 40%, and the degree of oxidation of OHA in component B was adjusted from 30% to 40%. The preparation method of the wound dressings in Examples 7-8 is the same as that in Example 1.
[0085] Examples 9-10 Two embodiments of the sonodynamic antibacterial quantum dot spray film-forming wound dressing and its preparation method are provided in this invention. The wound dressings in Embodiments 9-10 differ from those in Embodiment 1 only in the volume ratio of component A to component B, the content of quantum dots, and the pH value. Specifically: Example 9: Compared with Example 1, the volume ratio of component A to component B in the wound dressing of Example 1 was adjusted from 1:1 to 0.5:1, the mass fraction of hydrophilic ZnS:Ag QDs in the wound dressing was adjusted from 0.05% to 0.01%, and the pH value of component A to component B was adjusted from 6.8 to 6.0; Example 10: Compared with Example 1, the volume ratio of component A to component B in the wound dressing of Example 1 was adjusted from 1:1 to 2:1, the mass fraction of hydrophilic ZnS:Ag QDs in the wound dressing was adjusted from 0.05% to 0.2%, and the pH value of component A to component B was adjusted from 6.8 to 7.5; The preparation method of the wound dressings in Examples 9-10 is the same as that in Example 1.
[0086] Comparative Examples 1-2 This invention provides two comparative examples of a sonodynamic antibacterial quantum dot spray-formed wound dressing and its preparation method. The difference between the wound dressings in Comparative Examples 1 and 2 and those in Example 1 lies only in the content of EDA-HA in component A. Specifically, Comparative Example 1: Compared with Example 1, the mass fraction of EDA-HA in component A of Example 1 was adjusted from 7% to 1%; Comparative Example 2: Compared with Example 1, the mass fraction of EDA-HA in component A of Example 1 was adjusted from 7% to 30%, and the other conditions were the same as in Example 1.
[0087] The preparation methods of the wound dressings in Comparative Examples 1-2 are the same as those in Example 1.
[0088] Comparative Examples 3-4 The present invention provides two comparative examples of a sonodynamic antibacterial quantum dot spray-formed wound dressing and its preparation method. The wound dressings in Comparative Examples 3-4 differ from those in Example 1 only in the degree of oxidation of OHA in component B. Specifically, Comparative Example 3: Compared with Example 1, the oxidation degree of OHA in component B of Example 1 was adjusted from 30% to 10%; Comparative Example 4: Compared with Example 1, the oxidation degree of OHA in component B of Example 1 was adjusted from 30% to 45%; The preparation method of the wound dressings in Comparative Examples 3-4 is the same as that in Example 1.
[0089] Comparative Examples 5-6 The present invention provides two comparative examples of a sonodynamic antibacterial quantum dot spray-formed wound dressing and its preparation method. The wound dressings in Comparative Examples 5-6 differ from those in Example 1 only in the pH values of components A and B. Specifically, Comparative Example 5: Compared with Example 1, the pH values of components A and B in Example 1 were both adjusted from 6.8 to 5.2; Comparative Example 6: Compared with Example 1, the pH values of components A and B in Example 1 were both adjusted from 6.8 to 8.2; The preparation method of the wound dressings in Comparative Examples 5-6 is the same as that in Example 1.
[0090] Comparative Example 7 This invention provides a comparative example of a wound dressing with acoustically driven antibacterial quantum dot spray film and its preparation method. The only difference between this comparative example wound dressing and Example 1 is the acoustically driven antibacterial quantum dots. Compared with Example 1, the hydrophilic ZnS:Ag QDs in the wound dressing of Example 1 are adjusted to ZnS:Ag QDs (i.e., unhydrophilicated quantum dots). The preparation method of the wound dressing is the same as that of Example 1.
[0091] Comparative Example 8 This invention provides a comparative example of a wound dressing for acoustic-dynamic antibacterial quantum dot spray film formation and its preparation method. The only difference between this comparative example wound dressing and Example 1 is that the amino-modified hyaluronic acid in component A is different. Compared with Example 1, the amino-modified hyaluronic acid EDA-HA in component A of Example 1 is adjusted to hydrazide-modified hyaluronic acid (ADH-HA). The preparation method of the wound dressing is the same as that of Example 1.
[0092] Test Example 1 The wound dressings of the examples and comparative examples were evaluated for their pre-spray single-can component performance and post-spray film-forming performance. The pre-spray single-can component performance evaluation focused on component A, component A containing quantum dots, component B, or component B containing quantum dots, all loaded into the spray device. The post-spray film-forming performance evaluation focused on the film layers formed on the substrate surface after the application of components A and B.
[0093] The dispersion stability of quantum dots in the A and / or B components of the wound dressings containing quantum dots in the examples and comparative examples was tested, with the A and / or B components containing quantum dots sprayed separately after canning as the evaluation objects.
[0094] The spraying devices used in the examples and comparative examples were all high-pressure aerosol cans without carryover agents, and the driving gas was nitrogen. The spraying distance for the sprayability test was 15 cm, and the spraying method was continuous valve pressing for 30 s. Unless otherwise stated, film formation observation was performed in a state perpendicular to the substrate (90°); the quantum dot dispersion stability observation time was 24 h at room temperature.
[0095] 1. Performance evaluation of single-can components before spraying (1) Stability of continuous spraying Under the conditions of a spray distance of 15 cm and continuous pressing for 30 s, the spray output is continuous without obvious interruption or change from atomized state to obvious jet / intermittent state, and is judged to be qualified for continuous spraying stability.
[0096] The specific determination is as follows: Acceptable: Within 30 seconds of continuous pressing, there is no "jet / intermittent" flow lasting longer than 3 seconds, and the spray does not completely stop; Unacceptable: Any "jet / intermittent" flow lasting longer than 3 seconds within 30 seconds, or spraying stops.
[0097] (2) Blockage situation A blocking event is defined as one of the following conditions: a. The spray transitions from an atomized state to a distinct jet and lasts for >3 seconds; b. The spraying is noticeably intermittent and lasts for >3 seconds; c. Spraying must be stopped and atomization can only be restored after disassembling or cleaning the nozzle and valve core.
[0098] The specific determination is as follows: Qualified: 0 blockage events within 30 seconds; Unacceptable: ≥1 blockage event within 30 seconds.
[0099] (3) Atomization uniformity The definition for determining atomization uniformity is as follows: a. The spray cone shape is stable, and the spray width shows no obvious drift; b. There is no obvious large droplet aggregation area in the sprayed area; where large droplet aggregation area is defined as: within a 10 cm × 10 cm area, there are no less than 3 droplets or water droplets with a diameter ≥ 1 mm; c. No jetting occurs within 30 seconds / Intermittent jetting > 3 seconds.
[0100] The specific determination is as follows: Qualified: Meets all three of the above requirements (AC). Unqualified: Does not meet any of the above AC requirements.
[0101] 2. Quantum dot dispersion stability Spray the single-canned components containing quantum dots A and / or B into a sealable transparent container and let stand at room temperature for 24 hours.
[0102] The specific determination is as follows: Acceptable: No obvious sedimentation layer is visible to the naked eye after standing at room temperature for 24 hours; or although there is slight sedimentation, it can be completely re-dispersed after gentle shaking or inverting 10 times; and there are no visible flocculent aggregates.
[0103] Unacceptable: When left to stand at room temperature for 24 hours, a significant sedimentation layer appears and cannot be dispersed again after gentle shaking or inverting the container 10 times, or flocculent agglomerates or particle agglomerates appear.
[0104] 3. Evaluation of film-forming performance after spraying The two components of the wound dressings from the examples and comparative examples were sequentially sprayed onto the substrate surface to form a film layer according to the actual usage method, and the resulting film layer was evaluated.
[0105] (1) Film formation time Film formation time (t1) is defined as the time point at which the film layer reaches a stable film-forming state when the coating is completed at a vertical 90° angle. A stable film-forming state means that no visible flow occurs in the film layer, and the film surface is continuous without obvious sagging, local accumulation, gel clusters, or discontinuous areas. A stopwatch is used to record the time from the end of spraying to the stable film-forming state.
[0106] The specific determination is as follows: Qualified: 30s≤t1≤180s, and the film layer is continuous and uniform; Unacceptable: t1 > 180 s, or although it loses fluidity within 180 s, it shows obvious gel clusters, streaks, local accumulation, or discontinuous film layers; when t1 < 30 s and is accompanied by local premature gelation, gel clusters, streaks, or uneven film layers, it is also considered unacceptable.
[0107] (2) Film formation uniformity The definition of film uniformity is as follows: a. When viewed directly, the membrane surface shows no obvious streaks, pinholes, or gel clusters; b. When viewed from the side, the membrane surface has no obvious unevenness or steps, and there are no visible particles; where particles are defined as gel clusters with a diameter ≥ 1 mm.
[0108] The specific determination is as follows: Qualified: Both options a and b are met simultaneously; Unqualified: Does not meet any of the criteria in ab.
[0109] (3) Slippage After spraying and during the period of film stabilization, the observation period is up to 180 seconds. If the film layer is placed vertically and the whole or the edge moves downward to form flow marks, the downward movement distance is ≤2 mm and is considered qualified; the downward movement distance is >2 mm and is considered unqualified.
[0110] (4) Wet adhesion / interlocking performance After the film has stabilized and formed, take a film sample of about 5 cm × 5 cm and hold it at a 90° angle. Pour room temperature water from a height of about 10 to 20 cm above the sample and rinse it. Each time, the water should last for about 5 to 10 seconds (about 50 mL of water). Repeat this process 3 times.
[0111] The specific determination is as follows: Acceptable: The membrane layer does not fall off completely after rinsing, and the downward displacement of the membrane layer is ≤2 mm, and the area of edge lifting or falling off is ≤10%; Unqualified: The entire film layer peels off, or shifts downward by more than 2 mm, or the peeling area is greater than 10%.
[0112] (5) Uniformity of quantum dot distribution within the film After the film has stabilized, it is illuminated with white light at a 45° angle from a distance of about 30 cm. The bright spots, dark spots, or color difference spots on the surface of the film are observed with the naked eye. If there are no bright spots, dark spots, or color difference spots with a diameter ≥1 mm in a 10 cm × 10 cm area, it is considered qualified. If there are bright spots, dark spots, or color difference spots with a diameter ≥1 mm, or if the spots are connected into stripes, it is considered unqualified.
[0113] The performance test results of the wound dressings of Examples 1-10 and Comparative Examples 1-8 are shown in Tables 1-1 and 1-2. The spray performance and quantum dot stability results of the single-can components are shown in Table 1-1, and the film-forming performance results are shown in Table 1-2.
[0114] Table 1-1 Table 1-2 Table 1 shows that, under the conditions of a spray distance of 15 cm and continuous pressure for 30 s, any single component of the two-component wound dressing in the embodiment produced continuous spray output without significant interruption or change from atomized state to obvious jet / intermittent state, indicating qualified continuous spraying stability; there was no clogging in the spray; the spray cone shape was stable, the spray width did not drift significantly, and there was no obvious large droplet aggregation area in the sprayed area, indicating qualified atomization uniformity; after standing at room temperature for 24 h, there was no obvious sedimentation layer visible to the naked eye; or although there was slight sedimentation, it could be completely re-dispersed after gentle shaking or inversion 10 times, and there were no visible flocculent agglomerates, indicating qualified quantum dot dispersion stability.
[0115] The two-component wound dressing of the embodiment can form a stable and continuous film within 30s to 180s after spraying. The film surface is free of obvious streaks, pinholes, and gel clumps, and there are no obvious unevenness or steps or visible particles. The film uniformity is good. After spraying and during the period of film stabilization (within 180s), the film layer does not move significantly downward as a whole or at the edges when placed vertically, or the downward movement does not exceed 2 mm, and the sagging is qualified. After the film has stabilized, the film sample is held at a 90° angle and splashed with water. The film layer does not fall off completely, the downward movement of the film layer is ≤2 mm, and the area of edge lifting or falling off is ≤10%, and the wet adhesion / interlocking performance is qualified. At the same time, the film layer has good uniformity.
[0116] In Comparative Example 1, the mass fraction of EDA-HA in component A of the two-component wound dressing was below a specific range. Although the continuous spraying stability, clogging, atomization uniformity, and quantum dot dispersion stability of any single component were all qualified, the film-forming time, film-forming uniformity, sagging, wet adhesion / interlocking performance, and intra-film distribution uniformity were all unqualified. In Comparative Example 2, the mass fraction of EDA-HA in component A was above a specific range. The continuous spraying stability, clogging, and atomization uniformity of component A were unqualified, and the film-forming time, film-forming uniformity, wet adhesion / interlocking performance, and intra-film distribution uniformity were all unqualified.
[0117] As can be seen from Comparative Examples 1-2, the mass fraction of EDA-HA in component A of the wound dressing of the present invention needs to meet a specific range.
[0118] In Comparative Example 3, the oxidation degree of OHA in component B of the two-component wound dressing was below a specific range. Although the continuous spraying stability, clogging, atomization uniformity, and quantum dot dispersion stability of any single component were all qualified, a stable continuous film layer could not be formed within 180 s. Film formation time, film uniformity, sagging, wet adhesion / interlocking performance, and intra-film distribution uniformity were all unqualified. In Comparative Example 4, the oxidation degree of OHA in component B of the two-component wound dressing was above a specific range. Although the continuous spraying stability, clogging, atomization uniformity, and quantum dot dispersion stability of any single component were all qualified, film uniformity, wet adhesion / interlocking performance, and intra-film distribution uniformity were all unqualified due to premature local gelation.
[0119] As can be seen from Comparative Examples 3-4, the oxidation degree of OHA in component B of the wound dressing of the present invention needs to meet a specific range.
[0120] In Comparative Examples 5 and 6, the pH values of components A and B in the two-component wound dressings were either higher or lower than a specific range. Consequently, the continuous spraying stability, clogging, atomization uniformity, and quantum dot dispersion stability all failed to meet standards. Furthermore, the film-forming time, film-forming uniformity, wet adhesion / interlocking performance, and intra-film distribution uniformity were all unsatisfactory. This indicates that the pH values of components A and B in the wound dressing of this invention need to meet a specific range. Specifically, when the pH is too low, cross-linking is insufficient and the stable film-forming time is prolonged; when the pH is too high, premature local gelation easily occurs, leading to uneven film layers.
[0121] The acoustic-dynamic antibacterial quantum dots in the two-component wound dressing of Comparative Example 7 were not hydrophilized. The continuous spraying stability, clogging, atomization uniformity and quantum dot dispersion stability were all unqualified. Furthermore, the film uniformity, wet adhesion / interlocking performance and intrafilm distribution uniformity were also unqualified. This indicates that the acoustic-dynamic antibacterial quantum dots of the present invention should be hydrophilized acoustic-dynamic antibacterial quantum dots.
[0122] In Comparative Example 8, when the aminoated hyaluronic acid in component A of the two-component wound dressing was replaced with ADH-HA, the continuous spraying stability, clogging, and atomization uniformity all failed to meet standards. Furthermore, the film-forming time, film-forming uniformity, sagging, wet adhesion / interlocking performance, and intra-film distribution uniformity also failed to meet standards. This indicates that under the high-pressure aerosol spraying film-forming conditions of this invention without carryover agent, component A preferably uses EDA-HA; when ADH-HA is used instead of EDA-HA, it is difficult to simultaneously achieve stable atomization spraying and uniform film formation.
[0123] Test Example 2 Using the wound dressings of Examples 1-3 as representative samples, the antibacterial properties of the samples under ultrasound-triggered conditions were tested.
[0124] Staphylococcus aureus and Escherichia coli were used as test subjects to test the antibacterial properties of the wound dressings in Examples 1-3 against these two bacteria. An experimental group, a quantum dot group (positive control group), and a blank control group were set up. The experimental group consisted of a wound dressing extract, the quantum dot group consisted of a hydrophilic ZnS:Ag QDs liquid culture medium dispersion with the same final quantum dot concentration as in Example 1, and the control group consisted of a liquid culture medium.
[0125] The preparation method of the wound dressing extract is as follows: Component A and Component B from Examples 1-3 are respectively placed in two high-pressure aerosol cans without carry-over agent, and sprayed into a film according to the actual use method. After the film layer is stabilized, an equal amount of film sample is cut and placed in a liquid culture medium, and extracted at 37°C for 24 h. The supernatant of the extraction is taken as the wound dressing extract.
[0126] The specific experimental steps are as follows: Staphylococcus aureus suspension (1×10^6 CFU / mL) and Escherichia coli suspension (1×10^6 CFU / mL) were prepared separately. The bacterial suspensions were added to the experimental group, quantum dot group, and blank control group, respectively, and treated under the same ultrasonic conditions to trigger the sonodynamic process of the quantum dots. Subsequently, they were incubated at 37℃ for 12 h. After incubation, the reaction solutions of each group were serially diluted 10-fold, and the appropriate dilutions were plated on agar plates. After incubation at 37℃ for 24 h, photographs were taken, and the colony counts of each group were compared.
[0127] Test results showed that, under ultrasound-triggered conditions, the wound dressings of Examples 1-3 exhibited good antibacterial properties against Staphylococcus aureus and Escherichia coli, indicating that the wound dressings of the present invention have a broad antibacterial spectrum. The effect of the wound dressing of Example 1 on Staphylococcus aureus on a spread plate is shown in the figure. Figure 7 As shown, the wound dressing of Example 1 showed good results on Escherichia coli plating. Figure 8 As shown.
[0128] Test Example 3 Using the wound dressings of Examples 1-3 as representative samples, the in vitro cell compatibility of the samples was tested.
[0129] Using mouse fibroblasts (L929 cells) as the experimental subject, the compatibility of the wound dressings of Examples 1-3 with these cells was tested. An experimental group, a quantum dot group, and a blank control group were set up. The experimental group consisted of the wound dressing extract; the quantum dot group consisted of a hydrophilic ZnS:Ag QDs cell culture medium dispersion with the same final quantum dot concentration as in Example 1; and the blank control group consisted of L929 cells without any material treatment, but with an equal volume of L929 cell culture medium.
[0130] The preparation method of the wound dressing extract is the same as that of test example 2.
[0131] The specific experimental steps are as follows: L929 cells were seeded in 96-well plates and cultured overnight to allow them to adhere to the plate. Then, the solutions of the experimental group, quantum dot group and blank control group were added respectively, and incubation was continued for 24 h. After incubation, MTT reagent was added for further incubation. After discarding the supernatant, dimethyl sulfoxide was added to dissolve the formazan crystals, and the absorbance at 570 nm was measured. The cell viability of each group was evaluated based on this.
[0132] Test results showed that the wound dressings of Examples 1-3 did not exhibit significant cytotoxicity against L929 cells and demonstrated good in vitro cell compatibility. The MTT assay results for the wound dressing of Example 1 on L929 cells are as follows: Figure 9 As shown.
[0133] Test Example 4 Using the wound dressing from Example 1 as a sample, the effect of the sample on the burn wound repair process was tested.
[0134] SD rats were selected, anesthetized, had their back hair removed, and their skin disinfected. A burn wound model of the same area was established on the back. After modeling, the SD rats were randomly divided into a control group and an experimental group. In the control group, the burn wound was cleaned routinely and covered with gauze without any wound dressing. In the experimental group, the burn wound was cleaned routinely, and then the quantum dot-containing components A and B of Example 1 were sprayed sequentially onto the burn wound surface, forming a continuous film layer in situ. Both groups of rats were observed under the same feeding conditions, and the wounds were photographed and recorded at the same time points.
[0135] After the burn wound model was established, each group of wounds was photographed and recorded at time point D0. Then, the wounds were treated in the same way as the blank group and the experimental group. Subsequently, the changes in the appearance of the wounds were observed and photographed at D4, D8, D12, D22 and D36. The repair processes of each group of wounds, such as exudation, scab formation, wound shrinkage, granulation tissue formation and re-epithelialization, were compared.
[0136] Test results showed that, compared with the control group, the experimental group had a cleaner wound surface, a more obvious wound shrinkage trend, and a smaller residual wound area in the later stage during the repair process. This indicates that the wound dressing of the present invention can stably cover the burn wound and help the burn wound repair process.
[0137] The effect of the wound dressing in Example 1 on the burn wound repair process is as follows: Figure 10 As shown.
[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A wound dressing that uses acoustically driven antibacterial quantum dot spray to form a film, characterized in that, The wound dressing comprises separately packaged components A and B, as well as sonodynamic antibacterial quantum dots dispersed in components A and / or B. Component A is a solution containing ethylenediamined hyaluronic acid, which is obtained by reacting carboxyl-activated hyaluronic acid with ethylenediamine; the mass fraction of ethylenediamined hyaluronic acid in component A is 5%~20%; the degree of amination of ethylenediamined hyaluronic acid in component A is 15%~40%. Component B is a solution containing oxidized hyaluronic acid, with an oxidation degree of 15% to 40%; the mass fraction of oxidized hyaluronic acid in component B is 5% to 20%. The pH values of both component A and component B are 6.0 to 7.
5. The sonodynamic antibacterial quantum dots are hydrophilic sonodynamic antibacterial quantum dots.
2. The wound dressing as described in claim 1, characterized in that, The solvents for components A and B include water or buffer solutions; And / or, the volume ratio of component A to component B in the wound dressing is (0.5~2):1; And / or, the mass fraction of sonodynamic antibacterial quantum dots in the wound dressing is 0.01%~0.2%; And / or, the hydrophilized sonodynamic antibacterial quantum dots are hydrophilized by ligand exchange using hydrophilic ligands.
3. The wound dressing as described in claim 2, characterized in that, The mass fraction of ethylenediamined hyaluronic acid in component A is 5%~15%; the degree of amination of the ethylenediamined hyaluronic acid is 20%~35%. And / or, the mass fraction of oxidized hyaluronic acid in component B is 5%~15%; the degree of oxidation of the oxidized hyaluronic acid is 20%~35%; And / or, the mass fraction of sonodynamic antibacterial quantum dots in the wound dressing is 0.02%~0.15%; And / or, the hydrophilic acoustic-dynamic antibacterial quantum dots are hydrophilic silver-doped zinc sulfide quantum dots; And / or, the hydrophilic ligand includes mercaptopropionic acid, mercaptoacetic acid, mono-mercaptopolyethylene glycol, or mercapto-polyethylene glycol-carboxyl.
4. The wound dressing as described in claim 3, characterized in that, The size of the hydrophilic silver-doped zinc sulfide quantum dots is 2~10 nm; And / or, the solution of component A and / or component B may also contain excipients; the excipients may include dispersants / stabilizers, moisturizers / plasticizers, osmotic pressure regulators, buffer solutions, or adhesion / wetting regulators.
5. The wound dressing as described in claim 4, characterized in that, The dispersant / stabilizer includes PVP, PEG, or poloxamer; And / or, the moisturizing / plasticizing agent includes glycerin, sorbitol, or propylene glycol; And / or, the osmotic pressure regulator includes NaCl; And / or, the buffer solution includes PBS buffer.
6. A method for preparing the wound dressing according to any one of claims 1 to 5, characterized in that, After aseptic treatment, components A and B are aseptically dispensed into a spraying device. Before aseptic treatment, hydrophilic acoustic antibacterial quantum dots are added to components A and / or B and dispersed evenly to obtain the wound dressing.
7. The preparation method according to claim 6, characterized in that, At least one of the following (I) to (III): (I) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component A from step S1 and disperse them evenly to obtain component A containing quantum dots. S4. Sterilize the quantum dot-containing component A from step S3 and the component B from step S2, and then aseptically dispense them into the spraying device to obtain the wound dressing. (II) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component B from step S2 and disperse them evenly to obtain component B containing quantum dots. S4. Sterilize the quantum dot-containing component B from step S3 and the component A from step S1, and then aseptically dispense them into the spraying device to obtain the wound dressing. (III) The preparation method includes the following steps: S1. Prepare component A using the raw materials of component A; S2. Prepare component B using the raw materials of component B; S3. Mix the hydrophilic acoustic antibacterial quantum dots with component A of step S1 and component B of step S2 respectively, and disperse them evenly to obtain component A containing quantum dots and component B containing quantum dots. S4. The quantum dot-containing component A and quantum dot-containing component B from step S3 are sterilized separately, and then aseptically dispensed into a spraying device to obtain the wound dressing.
8. The preparation method according to claim 7, characterized in that, Before mixing with component A and / or component B, the hydrophilic acoustic antibacterial quantum dots are first dispersed evenly using a dispersant / stabilizer or a solvent for component A and / or component B. And / or, the spraying device is a high-pressure aerosol can.
9. The use of the wound dressing according to any one of claims 1 to 5 in the preparation of a dressing product for treating burn wounds.
10. A dressing product for burn wounds, characterized in that, A dressing product is formed by self-crosslinking of the wound dressing as described in any one of claims 1 to 5.
Citation Information
Patent Citations
PDA (at) Ag (at) Ag2S / SA / F68 / F127 antibacterial temperature-sensitive hydrogel as well as preparation method and application thereof
CN121550472A
Preparation method and application of ultrasonic response antibacterial hydrogel
CN121926867A